EEG alpha power during maintenance of information in working memory in adults with ADHD and its plasticity due to working memory training: A randomized controlled trial. Issue 2 (February 2016) - Liu, Zhong-Xu; Glizer, Daniel; Tannock, Rosemary; Woltering, Steven
Highlights: Randomized controlled clinical trial investigating neural changes in alpha power after working memory training. Differences in alpha power between ADHD and non-ADHD students, and changes after treatment, were marginally significant and had low effect sizes. Findings suggest that alpha power could not reliably distinguish between ADHD and non-ADHD, nor trace treatment effects, in the present sample. Abstract: Objective: The present study examined whether neural indices of working memory maintenance differ between young adults with ADHD and their healthy peers (Study 1), and whether this neural index would change after working memory training (Study 2). Methods: Study 1 involved 136 college students with ADHD and 41 healthy peers (aged 18–35 years) and measured their posterior alpha activity during a visual delayed-match-to-sample task using electroencephalography (EEG). Study 2 involved 99 of the participants with ADHD who were randomized into a standard-length or shortened-length Cogmed working memory training program or a waitlist control group. Results: The ADHD group tended to be less accurate than the peers. Similarly, the ADHD group exhibited lower posterior alpha power at a trend level compared to their healthy peers. There were no training effects on participants' performance and only marginal increases in posterior alpha power in training groups compared to the waitlist group. Conclusions: Considering that the training effects were small and there was no load and dose effect, we conclude that the current study provides no convincing evidence for specific effects of Cogmed. Significance: These findings provide unique insights into neuroplasticity, or lack thereof, with near-transfer tasks in individuals with ADHD.